Research trends on the relationship between parenting and prosocial behaviors in children and adolescents - Gómez Tabares, Anyerson Stiths; Montoya Arenas, David Andrés; Correa Duque, María Cristina` (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The parental role in the prosocial development of children and adolescents is a relevant topic in the social sciences. Although psychology has investigated parental competencies and prosocial behaviors, its research trends have not been analyzed. The aim of this paper is to analyze the scientific production and research trends on the relationship between parenting and prosocial behaviors in children and adolescents. The bibliographic search was carried out in the Web of Science database. The bibliometrix, Sci2 Tool and Gephi tools were used. The results highlight the current importance of contextual and intercultural factors in the study of parenting and prosocial development. The main research trends focused on the analysis of the mediation of emotional and moral factors between parenting practices and prosocial behavior in adolescents; parenting and psychological factors associated with prosocial development in childhood; and parenting practices associated with prosocial and antisocial behavior in adolescents. It is concluded that psychological factors such as empathy, positive affect and emotional self-efficacy, as well as family values, influence prosocial development in children and adolescents through positive parenting practices and styles.